الزمن النحوي و دلالاته في سورة الكهف - الأطرش, الأطرش, الزهرة الحادة (Univesity of El-Oued, 2022)
يعدُّ الزّمن من أهم المقولات النحوية في نظرية النحو العربي. فالصيغة الصرفية مفردة لا تكفي لتحديد الزّمن النحوي بدقّة؛ إذ إنّ هناك عناصر أخرى تتضافر معها لتحديد الزّمن وجهته في الجملة، وهذه العناصر إمّا أن تكون أدوات نحوية، أو سياقية، أو مقاميّة. وقد سعت هذه الدراسة الموسومة "الزّمن النّحوي ودلالاته في سورة الكهف" إلى البحث في الدلالات الزّمنيّة في الخطاب القرآني بغرض الكشف عن زمنها النحوي، وجهاته.the time is one of the important gramatical quotes in the Arabic grammar theory, the morphological form is not enough to determine exactly the grammatical time. As there are other elements combine with here to define the time and its aspect in the sentence. these elements are grammatical or contextual or pragmatic tools. this tagged study entitled "the grammatical time and its implications in the Surat ELKAHF" sought to search for the temporal connotations in Quranic discours in order to discover its grammatical time and its aspect.
Keywords: الزّمن الصرفي/ الزّمن النّحوي/ الجهات الزّمنية /اللغة العربية / سورة الكهف.; The morphological time/ the grammatical time/aspect/ the Arabic language/ Surat ELKAHF